Religious Organizations and Homosexuality: The Acceptance of Gays and Lesbians in American Congregations - Whitehead, Andrew L. (Review of religious research, 2013)
The participation of gays and lesbians in all aspects of society is continually disputed in the United States. Religion is one of the key battlegrounds. The extent to which religious congregations include lesbians and gays in congregational life is vital to the wider debate over homosexuality because congregations consistently influence more Americans than any other voluntary social institution reported by Putnam (Bowling alone: the collapse and revival of American community, Simon and Schuster, New York, 2000). Using nationally representative data from the 2006–2007 National Congregations Study this analysis investigates the level of acceptance of gays and lesbians within congregations as well as which congregations are most likely to allow lesbians and gays to become involved. I find that religious tradition, theological and political ideology, location, and demographic composition of congregations all influence the degree to which gays and lesbians are included into congregational life.